PERANCANGAN PRIVATE CLOUD COMPUTING MENGGUNAKAN OWNCLOUD - Wiyono, Pieter; Maslan, Andi (LPPM Universitas Putera Batam, 2021)
Cloud computing has an important role for development of technology. Cloud computing is the use of internet network technology to become a central server for managing and storing data. Cloud computing is very useful, especially for large companies, because it saves more data storage space, data is also safer than those who still store data in conventional ways such as using a flash or hard disk. In addition, by using cloud storage, users such as employees in companies can send data to each other quickly, so they can save time and be more efficient in their performance. The problems that are transported are how users can store and exchange data, the process of designing cloud storage, and also utilizing cloud storage services. The purpose of this research is to design, implement, and evaluate private cloud storage. Based on the objectives, the result of this research is the system design is done using PHP to design the web interface. From the web interface it is connected to OwnCloud using the REST API protocol. After that, the private cloud storage system is implemented in a company and evaluated so that it gets a system that can run and function properly.